Barriers and facilitators for treatment and control of high blood pressure among hypertensive patients in Kathmandu, Nepal: a qualitative study informed by COM-B model of behavior change - Buna Bhandari; Padmanesan Narasimhan; Abhinav Vaidya; Madhusudan Subedi; Rohan Jayasuriya (BMC, 2021)
Abstract Background Nepal has a high prevalence of hypertension which is a major risk factor for cardiovascular diseases globally. It is inadequately controlled even after its diagnosis despite the availability of effective treatment of hypertension. There is a need for an in-depth understanding of the barriers and facilitators using theory to inform interventions to improve the control of hypertension. This formative study was conducted to address this gap by exploring the perceived facilitators and barriers to treatment and control of hypertension in Nepal. Methods We conducted in-depth interviews (IDIs) among hypertensive patients, their family members, healthcare providers and key informants at primary (health posts and primary health care center) and tertiary level (Kathmandu Medical College) facilities in Kathmandu, Nepal. Additionally, data were collected using focus group discussions (FGDs) with hypertensive patients. Recordings of IDIs and FGDs were transcribed, coded both inductively and deductively, and subthemes generated. The emerging subthemes were mapped to the Capability, Opportunity, and Motivation-Behaviour (COM-B) model using a deductive approach. Results Major uncovered themes as capability barriers were misconceptions about hypertension, its treatment and difficulties in modifying behaviour. Faith in alternative medicine and fear of the consequences of established treatment were identified as motivation barriers. A lack of communication between patients and providers, stigma related to hypertension and fear of its disclosure, and socio-cultural factors shaping health behaviour were identified as opportunity barriers in the COM-B model. The perceived threat of the disease, a reflective motivator, was a facilitator in adhering to treatment. Conclusions This formative study, using the COM-B model of behaviour change identified several known and unknown barriers and facilitators that influence poor control of blood pressure among people diagnosed with hypertension in Kathmandu, Nepal. These findings need to be considered when developing targeted interventions to improve treatment adherence and blood pressure control of hypertensive patients.